Your pregnancy and newborn journey : a guide for pregnant teens - Lindsay, Jeanne Warren; Brunelli, Jean (Buena Park, Calif. : Morning Glory Press, 1998)
Discusses nutritional, medical, and social aspects of teenage pregnancy and teenage parenthood.
Keywords: Prenatal care -- Juvenile literature; Teenage pregnancy -- Juvenile literature; Teenage parents -- Juvenile literature; Pregnancy; Teenage parents